O divertimento nos espaços associativos de imigrantes alemães e teuto-brasileiros em Juiz de Fora-MG: do último quartel do séc. XIX ao fim da II Guerra Mundial - Jakeline Duque de Moraes Lisboa (2017)
This thesis aims to understand, within the urban fabric of Juiz de Fora, a city in the state of Minas Gerais, the entertainment at associative spaces of the German and German-Brazilian immigrants. Juiz de Fora was chosen due to the migratory flow of this ethnic group to the city, to its economic participation and, mainly, its contribution to the construction of an urban sociability through the opportunity of entertainments offered at the associative spaces located at different places in the city between the final decades of the nineteenth century and the first half of the twentieth century. Until now, we have seen few studies intended to analyze these spaces, although in none of them we could identify the topic proposed in this work. Therefore, we analyzed the forms of entertainment offered by breweries of immigrants as well as the process of starting clubs, motivated by the practices enjoyed in these spaces, using newspapers, photographs and various documents as research sources. We have observed that the associative spaces of immigrants were essential in maintaining their culture and that the entertainments provided allowed the local society the knowledge and socialization of different practices by encouraging the urban sociability and, as a result, boosting the cultural dynamism of the city.